EXPLORING MUHAMMADIYAH’S HISTORICAL CIVILIZATIONAL DIMENSION OF SOCIAL RECONSTRUCTION IN INDONESIA: HUMANITARIAN AND COSMOPOLITAN APPROACHES - Khoirudin, Azaki; Baidhawy, Zakiyuddin; Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2020)
This study aims at describing the civilizational dimension of Muhammadiyah’s contribution which has not made an adequate attention. By the use of historical-philosophical approach and educational theories of social reconstruction, this paper, argues that the educational thought of Muhammadiyah is always influenced by the dynamic and religious development thought (ideology) emerging in Muhammadiyah. This paper is using a qualitative approach, where most of the data were collected through a library research mechanism. This study shows that first, Muhammadiyah education is a modern Islamic education which is based on the spirit of Islam Berkemajuan [Progressive Islam] aiming to reconstruct a timeworn public order to a new society. Therefore, Islam Berkemajuan is not only monolithic in its sociological reality but also expands its meaning to reconstruct the social economic, political and cultural development according to the age. Second, the Muhammadiyah’s philosophy of education is based on two foundations, namely the theology of al-Ma'un and the theology of al-‘Ashr which both of them are derived from the idea of KH. Ahmad Dahlan, the founder of Muhammadiyah. Both the theological bases become the anchor of the thinking and practice of the education of Muhammadiyah. Third, the purpose of education in Muhammadiyah is that to grow or develop the "Ma’rifat quotient" (the consciousness of divinity) which later becomes the cornerstone of the birth of the cosmopolitan and humanitarian ethos of Muhammadiyah. Both of the ethics manifest in the work of the Muhammadiyah social issues of civilization, health, economic, political, philanthropic, disaster relief, community empowerment and many others.